2009
DOI: 10.1257/mac.1.2.225
|View full text |Cite
|
Sign up to set email alerts
|

How Is Foreign Aid Spent? Evidence from a Natural Experiment

Abstract: We use oil price fluctuations to test the impact of transfers from wealthy OPEC nations to their poorer Muslim allies. The instrument identifies plausibly exogenous variation in foreign aid. We investigate how aid is spent by tracking its short-run effect on aggregate demand, national accounts, and balance of payments. Aid affects most components of GDP though it has no statistically identifiable impact on prices or economic growth. Much aid is consumed, primarily in the form of imported noncapital goods. Aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
120
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 21 publications
10
120
2
Order By: Relevance
“…Extant approaches addressing this problem rely on instrumental variables (IVs) that are likely to be related to the outcome through channels other than IMF programs and thus violate the exclusion restriction. To fill this gap, I employ a novel identification strategy for IMF programs inspired by recent methodological innovations (Nunn and Qian 2014;Werker, Ahmed, and Cohen 2009). I exploit exogenous variation over time in the IMF's liquidity and interact this variable with a country's probability of participating in IMF programs, thereby introducing variation across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Extant approaches addressing this problem rely on instrumental variables (IVs) that are likely to be related to the outcome through channels other than IMF programs and thus violate the exclusion restriction. To fill this gap, I employ a novel identification strategy for IMF programs inspired by recent methodological innovations (Nunn and Qian 2014;Werker, Ahmed, and Cohen 2009). I exploit exogenous variation over time in the IMF's liquidity and interact this variable with a country's probability of participating in IMF programs, thereby introducing variation across countries.…”
Section: Introductionmentioning
confidence: 99%
“…But this is precisely the behavior the Ramsey model refutes by explaining that households will respond so as to keep the economy on the steady state growth path. Werker et al (2009) provide empirical corroboration by showing that exogenous foreign aid payments go largely toward increasing consumption rather than investment. …”
Section: Exogenous Shocks: Simple Theorymentioning
confidence: 68%
“…Hansen and Tarp (2000) review previous studies and conclude that, in small amounts, aid can help growth rates. But Easterly (2004) warns that these results are fragile to definitions of growth, aid, and "good" institutions and Werker et al (2009) argue that most instruments for foreign aid are flawed. Most importantly, these papers look at the increase in the growth rate over a very short period (typically 4 years) concurrent with the increase in aid.…”
mentioning
confidence: 99%
“…The failure of foreign aid may due to various factors, such as poor governance of foreign aid funding, inefficient and unfair aid distribution amongst the recipient countries, conditional requirements of donor countries, political instability in the recipient countries (Dollar and Kraay, 2001;Inanga, 2008;Younas, 2008;Brück and Xu, 2012;Kalyvitis et al, 2012a;Kalyvitis and Vlachaki, 2012b;Raschky and Schwindt, 2012). Furthermore, there are some studies that have found ambiguous or mixed relationship between foreign aid and growth in the poor countries (Inanga and Mandah, 2008;Werker et al, 2009;Ekanayake and Chatrna, 2010). Holder (2004) argues that the relationship between foreign aid and growth turns out to be an inverted-U shaped under reasonable policy assumption, which is an Aid Laffer Curve.…”
Section: Introductionmentioning
confidence: 99%